Effects of positive emotion, extraversion, and dopamine on cognitive stability‐flexibility and frontal EEG asymmetry. (17th March 2017) - Wacker, Jan
Abstract: The influence of positive emotions on the balance between cognitive stability and flexibility has been suggested to (a) differ among various positive emotional/motivational states (e.g., of varying approach motivation intensity), and (b) be mediated by brain dopamine (DA). Frontal EEG alpha asymmetry (ASY) is considered an indicator of approach motivational states and may be modulated by DA. The personality trait of extraversion is strongly linked to positive emotions and is now thought to reflect DA‐based individual differences in incentive/approach motivation. The present study independently manipulated positive emotion (high approach wanting‐expectancy [WE] vs. low approach warmth‐liking [WL]) and dopamine (placebo vs. DA D2 blocker sulpiride) to examine their effects on both cognitive stability‐flexibility and emotion‐related ASY changes. The results showed numerically lower stability‐flexibility in WE versus WL under placebo and a complete reversal of this effect under the D2 blocker, no differentiation between WE and WL groups in terms of emotion‐related ASY change, but an association between self‐reported WE and WL and ASY changes toward left and right frontal cortical activity, respectively. Finally, extraversion was positively associated with both stability‐flexibility and ASY changes toward left frontal cortical activity under placebo, and these associations were completely reversed under the D2 blocker. The results (a) support a dopaminergic basis for frontal EEG asymmetry, extraversion, and the modulating effect of positive emotions on stability‐flexibility, and (b) extend previous reports of cognitive differences between introverts and extraverts.